2009
DOI: 10.1111/j.1467-8551.2008.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Firm: How Dynamic and Operating Capabilities Interact to Enable Entrepreneurship

Abstract: In this study, we expand our understanding of firm evolution by focusing on how operating and dynamic capabilities interact through endogenously led changes. The focus on endogenous change complements the current emphasis in the literature on how dynamic capabilities help firms cope with the risk of core rigidities following an exogenous shock. Our comparison of two collaborating firms shows that, at the operating capability level, firms build absorptive capacity in value networks during their product developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
178
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(204 citation statements)
references
References 47 publications
8
178
0
10
Order By: Relevance
“…Previous studies have suggested that exogenous shocks can induce substantial change (Newey and Zahra, 2009;Vergne and Durand, 2010;Li and Tallman, 2011;Paruchuri and Ingram, 2012). The empirical findings in this study support existing knowledge by illustrating that such external pressures indeed represent powerful agents of change that positively affect path dependency.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have suggested that exogenous shocks can induce substantial change (Newey and Zahra, 2009;Vergne and Durand, 2010;Li and Tallman, 2011;Paruchuri and Ingram, 2012). The empirical findings in this study support existing knowledge by illustrating that such external pressures indeed represent powerful agents of change that positively affect path dependency.…”
Section: Discussionsupporting
confidence: 79%
“…After a review of some of the numerous definitions of DC (Barreto, 2010;Eisenhardt & Martin, 2000;Newey & Zahra, 2009;Teece et al, 1997;Wang & Ahmed, 2007;Winter, 2003;Zott, 2003;among others), the definition of DC in this paper is "the firm's capacity to reconfigure its operational capabilities".…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The authors attempt to identify possible combinations of the three organizational capabilities and propose and analyze a sequence for creating superior customer value (Barreto, 2010;Eisenhardt & Martin, 2000;Newey & Zahra, 2009;Teece, Pisano, & Shuen, 1997;Wang & Ahmed, 2007;Zahra, Sapienza, & Davidsson, 2006;Zott, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A number of operations management researchers claim that, while competitive capabilities at the manufacturing firm level are defined as cost, quality, delivery reliability, and speed of delivery, operations-level capabilities should refer to routines (Ghosh, 2001;Schroeder et al, 2002). Capabilities building is linked mainly to the influence on organisational routines at the individual, organisational and network levels, which include customer/supplier integration and competitors (Capaldo, 2007;Newey & Zahra, 2009;Lisboa, Skarmeas & Lages, 2011;Capaldo & Messeni, 2011). Stephen et al (2015) point out that process management consists of three dimensions, which are process control, incremental process improvement and radical process improvement.…”
Section: Linking Routines To Capabilities In Operations Managementmentioning
confidence: 99%